SIMULATION FOR EFFECT OF MULTILAYER INTERPHASE ON TRANSVERSE CRACKING OF CERAMIC MATRIX COMPOSITES - REN JiaCheng; FANG GuangWu; ZHONG Yi; GAO XiGuang; SONG YingDong (Jixie qiangdu)
The effect of multilayer interphase on the transverse cracking behavior of ceramic matrix composites（ CMCs） was simulated by micromechanical finite element method. The sub-layers of interphase were created according to their real thickness within a RVE model to describe the microstructure of multilayer interphase of CMCs. The finite element method was applied to analysis the stress by defining different material properties for the interphase sub-layers. On this basis,the cracking and debonding were simulated by extended finite element method and cohesive interfacial model,respectively.. After all,a simulation method for transverse cracking in the multilayer interphase was developed. The simulation results for cracking path within monolayer BN interphase,and multilayer interphase of different structure（ BN/Si C/BN and BN/Si C/BN/Si C/BN） were compared. It can be seen that the interfacial debonding occurs at the interface between fiber and interphase for CMCs with multilayer interphase. Moreover,the transverse cracking strain of multilayer interphase is higher than that of monolayer interphase and the location of cracks for the two cases is very different.